AlGaN/GaN-HEMTs with a breakdown voltage higher than 100 V and maximum oscillation frequency fsub max as high as 100 GHz - Mokerov, V. G.; Kuznetsov, A. L.; Fedorov, Yu. V.; Bugaev, A. S.; Pavlov, A. Yu; Enyushkina, E. N.; Gnatyuk, D. L.; Zuev, A. V.; Galiev, R. R.; Ovcharenko, E. N.; Sveshnikov, Yu. N.; Tsatsulnikov, A. F.; et al. (Semiconductors (Woodbury, N.Y.), 2009)
The N-Alsub 0.27Gasub 0.73N/GaN High Electron Mobility Transistors (HEMTs) with different gate lengths Lsub g (ranging from 170 nm to 0.5 mum) and gate widths Wsub s (ranging from 100 to 1200 mum) have been studied. The S parameters have been measured; these parameters have been used to determine the current-gain cutoff frequency fsub t, the maximum oscillation frequency fsub max, and the power gain MSG/MAG and Mason's coefficients were investigated in the frequency range from 10 MHz to 67 GHz in relation to the gate length and gate width. It was found that the frequencies fsub t and fsub max attain their maximum values of fsub t = 48 GHz and fsub max = 100 GHz at Lsub g = 170 nm and Wsub g = 100 mum. The optimum values of Wsub g and output power P out of the basic transistors have been determined for different frequencies of operation. It has also been demonstrated that the 170 nm Alsub 0.27Gasub 0.73N/GaN HEMT technology provides both good frequency characteristics and high breakdown voltages and is very promising for high-frequency applications (up to 40 GHz)